Penilaian Wisatawan akan Atribut Pariwisata di Kota Batu - Abdullah, Taufik (THE Journal : Tourism and Hospitality Essentials Journal, 2017)
Batu City is one of the famous tourist destinations in Indonesia and has many tourism potentials. From 2011 to 2015 data on the number of domestic tourists who came to Batu City are fluctuated and leads to decline. Based on this phenomenon, this study was conducted. This study aimed to do the tourists’ assessment about tourism attributes in Batu City. This study is descriptive and qualitative. The number of respondents is 100 respondents who are domestic tourists in Batu City. The result of this study is hospitality attribute in Batu City got the highest average score among other attributes. Hopefully, this study could be a description for tourism stake holder in Indonesia especially Batu City to decide steps for planning tourism in the future.